Enhancing Behavioral Intention Through Improved Perceived Quality and Visitor Satisfaction - Abdullah, Mohammad Naufal Fauzan; Prameka, Adelia Shabrina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Efforts to increase customer satisfaction and create positive perceptions of the quality of a product or service offered. This decline is indicated by less than optimal customer satisfaction with the facilities and services provided. This explanatory quantitative study aims to analyze the influence of perceived quality on behavioral intention and visitor satisfaction, the influence of visitor satisfaction on behavioral intention, and the influence of perceived quality on behavioral intention through visitor satisfaction in the context of visitors to Speed Lane Go Karting. The sample consisted of 100 respondents selected using accidental sampling. The data were analyzed using path analysis, which shows that perceived quality influences behavioral intention, that perceived quality influences visitor satisfaction, that visitor satisfaction influences behavioral intention, and that perceived quality affects behavioral intention through visitor satisfaction. Therefore, it can be concluded that an improvement in perceived quality increases satisfaction, which in turn drives visitors’ positive behavioral intention. The novelty of this research is the use of visitor satisfaction as an intervening factor in the influence of perceived quality on behavioral intention. The practical implications of this research include the need to pay attention to the quality of services and facilities provided to visitors, including the completeness and security of gaming facilities, as well as customer comfort, which need to be continuously monitored and evaluate.